Exploring Learners’ Concept Understanding of Static Electricity: A Scientific Literacy Case Study in a Malaysian Primary School - Agung Wibowo; Fidia Fibriana; Nurzaimah Binti Asalal (Unnes Science Education Journal, 2025)
Understanding static electricity can be challenging for elementary students due to its abstract nature. As the ability to explain scientific phenomena is a key indicator of scientific literacy, contextual and interactive learning experiences are essential. This study aimed to explore the level of understanding of the concept based on a case study in a Malaysian primary school. This study investigated the implementation of a guided inquiry-based static electricity experiment and analyzed the scientific literacy outcomes of Grade 3 students in a Malaysian elementary school. Using purposive sampling, 28 students participated in a simple practicum that involved using a ruler and paper pieces, supported by a worksheet and a nine-item Likert-scale questionnaire to assess their scientific literacy. Data analysis confirmed normal distribution, with literacy scores indicating strong performance: 81% in understanding and explaining phenomena, 85% in designing and evaluating scientific inquiry, and 88% in applying scientific information for decision-making. Skewness values of 0.035, -0.836, and -0.917, respectively, suggest consistent data patterns. Despite overall positive results, the lowest score highlights the need to strengthen concept understanding. Findings demonstrate that simple, experiment-based learning can foster cognitive development and scientific literacy, emphasizing the role of teacher guidance in linking everyday experiences to scientific concepts.